VD_FINDINFO Décision / 2013 / 379 vom 16. April 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, PLAIGNANT, ASSISTANCE JUDICIAIRE, LÉSION CORPORELLE GRAVE | 125 al. 2 CP, 125 CP, 136 CPP (CH), 310 CPP (CH), 393 al. 1 let. a CPP (CH)